Impact of Field-Based Assignments on Students' Knowledge in the MBA Course in Ahmedabad City - Harshiv Parmar; Hiten Solanki; Jignesh Vidani (International Journal of Global Sustainable Research, 2024)
This study investigates the impact of field-based assignments on MBA students' knowledge and skills in Ahmedabad city, with a focus on understanding how such assignments enhance various academic and professional competencies. By analyzing the relationship between field-based assignments and students' perceptions of their learning outcomes, the research explores key areas such as the ability to apply classroom knowledge to real-world situations, problem-solving, communication skills, and career-specific competencies. The study also examines whether demographic factors, particularly age, influence students' perceptions of the effectiveness of these assignments. The results indicate that field-based assignments significantly enhance students' problem-solving abilities, communication skills, and engagement with the curriculum, with strong associations found between age and various learning outcomes, including improved analytical skills and real-world business insights. However, the study reveals weak correlations in areas like teamwork development, suggesting room for improvement in fostering collaboration through field-based assignments. Practical implications for MBA programs include the need to design field assignments that are closely aligned with industry requirements, tailored to diverse student profiles, and structured to improve both hard and soft skills. The study also highlights the importance of integrating real-world industry exposure and balancing workload demands. In conclusion, field-based assignments represent a crucial component of MBA education, offering students an effective platform to bridge theoretical knowledge with practical application, thereby better preparing them for challenges in the professional business environment